Dissemination of Carbapenem Resistant Pseudomonas aeruginosa among Burn Patients in Karbala Province\ Iraq - A. Shilba, Aseel; H. Al-Azzawi, Raghad; J. Al-Awadi, Salwa (Iraqi Journal of Science, 2023)
In this study, 158 clinical samples were collected from hospitalized burn patients during the period from December 2012 to June 2013 in Karbala province\ Iraq. Bacterial isolates were identified using conventional biochemical tests and then identification was confirmed by using Vitek-2 compact system. Pseudomonas aeruginosa recovery was 60 isolates in this study. These isolates were analyzed for antibiotic susceptibility by the disk diffusion test (DDT) according to Kirby Bauer's method using seven clinically important antipseudomonal agents: carbapenems (Imipenem and Meropenem), pencillins (Piperacillin), cephalosporins (Ceftazidim), monobactam (Aztreonam), quinolones (Ciprofloxacin) and aminoglycosides (Gentamicin). The results of resistance were as following: Imipenem 58.33%, Meropenem 66.67%, Piperacillin 86.67%, Ceftazidim 51.67%, Aztreonam 43.33%, Ciprofloxacin 46.67% and Gentamicin 91.67%. Antibiotic susceptibility test was confirmed by using VITEK-2 compact system. Differences between antibiotic susceptibility levels were calculated by Chi-square for each antibiotic. Results were highly significant for all antibiotic groups, p <0.01. The prevalence of increasing resistance rate to carbapenems, the final drug choice for the treatment of P. aeruginosa, among the immunocompromized burn patients is due to the increasing usage of this group especially Meropenem